The effect of sensationalised news on peoples' willingness to pay for food items - Chung, Jia Hui (Nanyang Technological University, 2021)
This study aims to evaluate the impact of different types of news articles on Singapore residents’ valuation of food items, which was obtained using the Contingent Valuation Method (CVM). The news articles focused COVID-19 food scares, and participants were categorized to either Treatment A (sensationalised news), Treatment B (scientific news) or Treatment C (control group) to read the relevant news articles respectively. The control group was not required to read any news articles. Following which, participants were asked their Willingness to Pay (WTP) for three different food items - pork shabu shabu, salmon steak and potatoes, each from two different countries, one affected by the COVID-19 food scare mentioned in the article and one not affected by the event. The results showed that there was a significant difference between the WTP of participants who read news and the participants who did not read any news, showing the impact of news, regardless of its nature. In addition, participants who read sensationalised news expressed a significantly lower WTP than participants who read scientific news, showing the importance in the way news is conveyed. Participants who read sensationalised news expressed a WTP which was $2.44 lower than the control group, and participants who read scientific news expressed a WTP which was $1.39 lower than the control group. A significant difference between the WTP for Treatment A and Treatment B was also found.